Perception and functionality of space in view of potential and dysfunction of senses: Sense-sensitive Architectural Design - Gawlak, Agata; Matuszewska, Magda; Ptak, Agnieszka; Priefer, Magdalena (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
This article is of an illustrative nature. It is intended to juxtapose the possible options of architectural perception and the potential capabilities and dysfunctions of senses. It is, further, aimed at highlighting the co-dependence of the perception of architecture on mental and physical abilities of man (its observer and user). The way space is perceived is dictated by the perceptual capabilities of our senses. Understanding the physiology and the role of the senses can sensitise the designers to the fact that the users’ responses to his/her works might diverge from the perceptual processes in the brain of the creator him/herself. More importantly, architecture itself can generate sensory feedback and exert a therapeutic effect in view of sensory dysfunctions.